Evolução das disponibilidades de alguns alimentos em Portugal de 1916 a 2000 - Durão, Catarina (2007)
This analysis studied the trends of some food availability in Portugal between 1916 and 2001, namely breadcereals (wheat, rye and maize), rice, potato, wine and olive oil. Additionally, the availability of legumeswas studied, but only for the period of 1936 till 2001.The availability of most foods decreased between de decade of 1916-1925 and the period of 1996-2001. Exceptionsto this rule were the availabilities of potato, rice and wheat, which increased by +318%, +100%and +59%, respectively.All other food availabilities decreased between 1916-1925 and 1996-2001. Maize's availability decreased (-83%), rye's availability decreased (-74%), as well as olive oil's (-17%) and wine's (0,3%) availabilities. Whereit concerns legumes, we concluded that, for the period of 1936-2001, its availability decreased 31%.